2016
DOI: 10.1093/nar/gkw848
|View full text |Cite
|
Sign up to set email alerts
|

H3K9me3 demethylase Kdm4d facilitates the formation of pre-initiative complex and regulates DNA replication

Abstract: DNA replication is tightly regulated to occur once and only once per cell cycle. How chromatin, the physiological substrate of DNA replication machinery, regulates DNA replication remains largely unknown. Here we show that histone H3 lysine 9 demethylase Kdm4d regulates DNA replication in eukaryotic cells. Depletion of Kdm4d results in defects in DNA replication, which can be rescued by the expression of H3K9M, a histone H3 mutant transgene that reverses the effect of Kdm4d on H3K9 methylation. Kdm4d interacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…Recent studies have shown that the chromatin context in which replication stress occurs can strongly influence DNA damage responses, with the preferential enrichment of γH2AX in heterochromatic regions marked by H3K9me3 31 , 38 , 39 . Furthermore, the modulation of chromatin structure and specifically H3K9me3 is able to modify DNA replication, restore repair capacity and suppress DNA damage 38 40 . We, therefore, ascertained the chromatin localisation of DNA damage observed following MMC in Vhl −/− MEFs and found that γH2AX foci were preferentially associated with H3K9me3-marked chromatin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the chromatin context in which replication stress occurs can strongly influence DNA damage responses, with the preferential enrichment of γH2AX in heterochromatic regions marked by H3K9me3 31 , 38 , 39 . Furthermore, the modulation of chromatin structure and specifically H3K9me3 is able to modify DNA replication, restore repair capacity and suppress DNA damage 38 40 . We, therefore, ascertained the chromatin localisation of DNA damage observed following MMC in Vhl −/− MEFs and found that γH2AX foci were preferentially associated with H3K9me3-marked chromatin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data shows that in the case of ccRCC, rescue of the replication stress response can be achieved through loss of the SWI/SNF chromatin remodeller PBRM1 and appears to be mediated, at least in part, through changes in H3K9me3-marked heterochromatin. H3K9me3 has been previously shown to play a critical role in linking chromatin structure to replication and the DDR response 31 , 40 , 47 . Furthermore, modulation of H3K9me3 can rescue the DNA repair defects observed with ATM deficiency 38 as well as the damage accumulation and early senescence associated with progeria 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wu et al. proposed a novel function of JMJD2D to facilitate DNA replication by reducing H3K9me3 ( 66 ), suggesting that hypoxic increase of H3K9me3 can influence DNA replication. Histone demethylases that play important roles in association with gene expression as well as with DNA replication can contribute to pathogenesis of hypoxia-related disease ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 Intriguingly, KDM4D, the H3K9me3 demethylase, is recruited to replication origins by ORC and MCM complexes, which further enlist Cdc45, PCNA and polymerases. 43 It was postulated that H3K9me3 levels were attenuated by Kdm4d to facilitate formation of the pre-initiation complex. Concomitantly, SUMOylation of ORC2 is also involved in recruiting KDM5A, the demethylase to convert H3K4me3 to H3K4me2, the ablation of which caused re-replication of the heterochromatin.…”
Section: Discussionmentioning
confidence: 99%